Discovery of novel bioactive peptides from spirulina (arthrospira) maxima - Montalvo, Grecia Esthefany Barriga (2018)
In the last years, the interest by the bioactive peptides Spirulina sp. (Arthrospira) is increasing, because of its Generally Regarded as Safe (GRAS) status, and their potential health benefits. These peptides can be used in different functional foods, for medical purposes, cosmetic and nutraceuticals, due to biological properties such as antihypertensive, antioxidative, anti-hyaluronidase and others. In the present investigation, Spirulina maxima were produced through of three hydrolyses process. After, the peptides fractions were purified through tangential filtration (membrane of 2 μM and 10kDa), and the fragments obtained below 10 kDa were partially characterized and determinate their antioxidant (radical scavenging, iron-chelating), antimicrobial, anti-inflammatory, and anti- collagenase. The peptide fraction obtained from the first hydrolyzed (PHA) presented antioxidant activity by capturing the DPPH radicals with a value of IC50 21.25 μg/ml and ABTS with IC50 9.5 μg/ml and TEAC 465.7 Trolox μM/μg sample, iron-chelating showed inhibition of 97.3% and IC50 6.99 μg/ml. Meanwhile, the peptide fraction obtained from the second hydrolyzed (PHP) presented antimicrobial activity with the half maximal inhibitory concentration (IC50) and the minimum bactericidal concentration (MBC) 0.34 mg/ml and 0.63 mg/ml (Bacillus subtilis), IC50 and MBC 0.62 mg/ml and 0.63 mg/ml (Staphylococcus aureus), IC50 and MBC 0.99 mg/ml and 1.25 mg/ml (Salmonella typhi), IC50 and MBC 0.94 mg/ml 1.25 mg/ml (Escherichia coli). The peptide fraction obtained from the two enzymes (PHS) showed antioxidant activity by capturing the DPPH radicals with a value of IC50 17.93 μg/ml and ABTS with IC50 8.6 μg/ml and TEAC 540.7 Trolox μM/μg sample, anti-inflammatory with inhibition of 39% and IC50 0.92 mg/ml, and anti-collagenase with inhibition 92.5% and IC50 32.49 μg/ml. The results indicated that protein isolate from Spirulina maxima can be a source for obtaining of peptides fractions (PHA, PHP and PHS) with activity antioxidants, iron-chelating, antimicrobial, anti-inflammatories and anti-collagenase.